1978
DOI: 10.2307/279632
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Pomacea Snails at Tikal, Guatemala

Abstract: Pomacea flagellata (Say), a large freshwater snail, was eaten by the ancient inhabitants of Tikal. Its shells appear in archaeological contexts datable to the entire circa 1500-year span of permanent occupation. Utilization was heaviest during the earliest and latest periods, a distributional pattern that seems directly related to population growth and decline. Comparison with the freshwater mussels and European land snails suggests that Pomacea snails were probably never more than a supplementary source of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…There is no sign of cooking or discoloration from heating on the surface, nor uniform piercing to extract the gastropod. This coincides with what previous studies have reported in the Peten [68]. It would appear that they were collected in dense quantities, regardless of size, and that the gastropods inside were removed in such a way that the shells were undamaged.…”
Section: The Classic Period Decline Of Freshwater Molluskssupporting
confidence: 91%
See 2 more Smart Citations
“…There is no sign of cooking or discoloration from heating on the surface, nor uniform piercing to extract the gastropod. This coincides with what previous studies have reported in the Peten [68]. It would appear that they were collected in dense quantities, regardless of size, and that the gastropods inside were removed in such a way that the shells were undamaged.…”
Section: The Classic Period Decline Of Freshwater Molluskssupporting
confidence: 91%
“…Significantly, this temporal invertebrate-vertebrate shift has been reported previously at other Maya sites, especially those with large faunal assemblages covering both the Preclassic and Classic periods. Moholy-Nagy was the first to report this trend at the large site of Tikal in the eastern Peten [68,69], noting that dense deposits of apple snails were only found during the Preclassic period. Similar patterns have been identified at Barton Ramie [70], Blue Creek [71], Cahal Pech [72], Cuello [73,74], K'axob [75], Pacbitun [76], San Bartolo-Xultun [77,78], and Yaxha-Sacnab [79], among others.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Evidence does exist for a shift away from exploitation of freshwater shellfish at the end of the Preclassic Period, however. This trend has been observed at Copan, Barton Ramie, possibly at Altar de Sacrificios, around Lakes Yaxha and Sacnab (54) and Tikal (55). A drying up of freshwater molluscan habitats is likely to produce such a sustained abstinence from escargot (56).…”
Section: The Impact Of Climatic Change On Groundwater Availabilitymentioning
confidence: 81%
“…The perennially or seasonally wet depressions formed by aguadas typically include sedges, ferns and grasses, and arboreal species that are common to transitional upland forests. Additionally, as freshwater ecosystems, aguadas act as important habitats to a number of mammals, avifauna, fish, gastropods and zooplankton (Goulden 1966; Lohse 2004; Moholy-Nagy 1978; Reyes 2004).…”
Section: Study Areamentioning
confidence: 99%